Application of FTIR Spectroscopy and Chemometric to Differentiate Azadirachta excelsa (Jack.) Jacobs Leaves Extracts Based on Solvent Polarity and Assessment of Antibacterial Activity - Adfa, Morina; Erliana, Dina; Wiradimafan, Khafit; Triawan, Deni Agus; Yudha S., Salprima; Avidlyandi, Avidlyandi; Rafi, Mohamad (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Azadirachta excelsa is a plant belonging to the same genus as the Indian neem (Azadirachta indica) which is expected to have similar biological activities. However, its active components and pharmacological effects are limited. The composition and quantity of these metabolites in A. excelsa may differ due to different polarities of extracting solvents, so selecting an effective extractive solvent with a high level of biological activity is important. Therefore, in this study, we examined differences in the metabolite finger printing using FTIR-based metabolomics, as well as evaluated their antibacterial activity against Staphylococcus aureus (ATCC 6538) and Escherichia coli (ATCC 8739). A. excelsa was extracted using chloroform, ethyl acetate, ethanol p.a., 70% and 50% ethanol. Extracts obtained were analyzed using FTIR and the inhibition zones were then determined. The results showed that principal component analysis (PCA) could distinguish each sample based on the extraction solvent. In this study, we found 50% and 70% ethanol extracts had similar metabolite compositions and concentrations based on their respective FTIR spectrum. The inhibition zone of A. excelsa extracts ranged from 12.37-17.20 mm and 13.88-15.89 mm against S. aureus and E.coli, respectively. The chloroform extract was more effective against both bacteria. Duncan's further test showed that chloroform extract reduced E. coli similarly to ethyl acetate but not S. aureus. While 50%, 70%, and ethanol p.a. extracts inhibited S. aureus and E. coli equally. Based on these results, the polarity of the extracting solvent had an important influence on the metabolite profile and antibacterial activity of A. excelsa. Keywords: Azadirachta excelsa, antibacterial activity, metabolite fingerprinting, FTIR.